Analisis Brand Equity Bina Nusantara University di Lingkungan SMU Jakarta - Retno Dewanti; Masruroh Masruroh; Doni B. (Bina Nusantara University, 2007)
This Research of Binus University brand equity have been conducted by using 5 elements of brand equity: brand awareness, brand association, perceived quality, brand loyalty, and market behavior. The research methodologies was descriptive, its explained perception of 3th level high school students from 10 privates as well public high schools in west Jakarta and east Jakarta. The result of this research was Binus university brand awareness was in top of mind level. There were 3 (three) associations of brand image of Binus, were IT up to date; complete and modern facilities; prestigious university which had high quality and innovative. Perceived quality element showed student’s expectations of university quality were overall most important. Brand loyalty element showed as reverse pyramid, that’s good loyalty for Binus University. Indicator of market behavior element showed 6,44% market share estimation.